(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2023)
This article expands upon a synthetic framework for examining affective-discursive responses to representations of race by drawing upon a merged framework of analyses of stance and emotional manifestation to advance the notion of how “emotional difficulties” shape and are shaped by readings of diversity. These difficulties show how and where potential growth and reflection on notions of inclusion and diversity occur. Student responses to images commonly found on international study office websites show the emotional tensions in interpretations of diversity representation using photo-elicitation techniques. In the analysis, individuals evaluated, positioned, and aligned themselves, relying on affective stances in three forms: uncritical acceptance, aggressive indifference, and wry amusement. The article argues that these emotional trends reveal student positions on inclusion and diversity in higher education and are an integral part of how students discursively and affectively navigate the embodied complexities of diversity representation.